Life and work of James Alexander Haldane - Wallace, D. E. (The University of Edinburgh, 1955)
Never before in the past century has there been such an active interest in evangelism, not only in the English speaking countries but on the Continent and in some sections of the Far East. Over ten of the leading graduate schools of theology in the United States are in the process of establishing or enlarging their departments of evangelism. One item conspicuous by its absence is the lack of material in the field of church history covering the subject of evangelism. These schools are handicapped at the very outset by a lack of research in this field. The following thesis is a study of the life and work of the one man who, above all others, led the way in establishing evangelism as a legitimate and necessary means of propagating the Gospel in Scotland. This work is neither an apology nor a vindication of this phase of church history. It is the product of research - diversified occurrences and facts - presented in narrative form. The delineation of the material requires more than a critical spirit; it is imperative that one possess a sympathetic understanding to see, in its proper perspective, the contribution of James Haldane to the improvement of the religious life of Scotland. The subject was marred by the defects caused by the taints of the times. He was dubbed narrow, purist, fanatic. We, however, would say after over a century has tried his works that he was a man of strong conviction, a Christian idealist, a man upon whom the spiritual destitution of the nation and the world lay heavy.
Keywords: Haldane, J. A. (James Alexander), 1768-1851; Evangelistic work; Baptists